Pelatihan Pembuatan Singkong Menjadi Keripik Singkong Varian Rasa - Mardiana Safitri; Hanifa Ayu B; Andika Surya G; Ardian Firnanda; Aisyah Nur W (Jurnal Informasi Pengabdian Masyarakat, 2023)
Indonesia is a tropical country that has the potential for diverse agricultural products in each region. Development in the field of entrepreneurship is one of the government's efforts to improve economic and community welfare evenly. H Selang is one of the villages in Bendungan District, Kapanewon Karangmojo, Gunung Kidul Regency, Yogyakarta Special Region Province. One of the agricultural products there is cassava. Usually cassava is only processed into krecek and used as animal feed. This makes the selling price low. Therefore, the KKN team innovated by utilizing these agricultural products into processed products with higher selling prices. The preparations are flavored cassava chips. The method for implementing this training consists of several methods, namely, socialization, discussion and practice. The aim of this training is to provide knowledge and processing of cassava. This training went smoothly and is expected to provide business opportunities for the local community and help the community market their commodity products more widely.